Prevalence of anxiety and risk associated with ventricular arrhythmia in patients with an implantable cardioverter defibrillator. (1st July 2020) - Habibović, M.; Pedersen, S.S.; Broers, E.R.; Alings, M.; Theuns, D.A.M.J.; van der Voort, P.H.; Bouwels, L.; Herrman, J.-P.; Denollet, J.
Abstract: Background: Anxiety has been associated with adverse clinical outcomes in patients who have received an implantable cardioverter defibrillator (ICD). However, results are inconclusive likely due to different measures being used to assess anxiety. Hence, the current study aims to examine the prevalence and the association between anxiety, ventricular tachyarrhythmia's (VTa's) and all-cause mortality, respectively. Methods: Patients who received an ICD for the first time were recruited from 6 Dutch referral hospitals as part of the WEBCARE trial. Patients filled in validated questionnaires (GAD-7, STAI-S, HADS-A, ANX4, ICDC, FSAS) to assess their baseline anxiety symptomatology. Logistic regression analysis and Cox Regression analysis were performed to examine the association between anxiety with 1) VTa's and 2) mortality, respectively. Results: A total of 214 Patients were included in the analysis with mean age 58.9 and 82.7% being male. The prevalence rates of anxiety varied depending on which questionnaire was used 12.4% (GAD-7), 17.5% (HADS-A), and 28.1% (STAI-S). (Cox) Regression analysis revealed that none of the anxiety measures was associated with VTa's or all-cause mortality in the current sample. Stratifying the sample by gender, the analysis showed that GAD-7, STAI-S, and ANX4 scores were associated with increased risk of VTa's but only in male patients. Conclusions: Prevalence rates of anxiety varied depending on the measurement tool used. No significant association between anxiety and VTa's and all-cause mortality was observed in the total sample. GAD-7, STAI-S, and ANX4 were associated with increased risk for VTa's but only in male patients. Highlights: Anxiety is highly prevalent in ICD patients. Anxiety is associated with ventricular arrhythmias in male ICD patients. Anxiety not associated with all-cause mortality in ICD patients Individual differences might explain inconsistent findings in previous studies.